1989
DOI: 10.1242/jcs.92.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocytes repel axons and cause axonal growth cone collapse

Abstract: We have examined the interactions between axons regenerating from dorsal root ganglia (DRGs) derived from newborn rats and oligodendrocytes cultured by three different techniques. Cultures examined after 2 days have a profuse outgrowth of axons from the DRGs, forming a dense mat on the culture surface. However, the axons avoid growing on oligodendrocytes; axons are seen all around these cells, but do not grow over them. We have also performed time-lapse video studies of the interactions between axonal growth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Differentiated oligodendrocytes in culture and CNS myelin exerted a strong inhibitory effect on adhesion and outgrowth for primary neurons, neuroblastoma cells, and also for spreading of nonneuronal cells (Caroni and Schwab, 1988b;McKerracher et al, 1994;Ng et al, 1996;Schwab and Thoenen, 1985). It was further shown that growth cones interacting with differentiated oligodendrocytes were inhibited in their fiber growth and forced to collapse (Bandtlow et al, 1990;Fawcett et al, 1989;Moorman and Gould 1997). In vivo experiments demonstrated that elongation of axons over long distances could be observed in myelin-free spinal cord or optic nerve, which has been produced by killing the dividing oligodendrocyte precursors by repeated X-irradiation of newborn rats (Savio and Schwab 1990;Weibel et al, 1994) or by immunocytolysis in chicken (Hasan et al, 1993;Keirstead et al, 1992).…”
Section: Cns Myelin a Nonconducive Environment For Extending Neuritesmentioning
confidence: 99%
“…Differentiated oligodendrocytes in culture and CNS myelin exerted a strong inhibitory effect on adhesion and outgrowth for primary neurons, neuroblastoma cells, and also for spreading of nonneuronal cells (Caroni and Schwab, 1988b;McKerracher et al, 1994;Ng et al, 1996;Schwab and Thoenen, 1985). It was further shown that growth cones interacting with differentiated oligodendrocytes were inhibited in their fiber growth and forced to collapse (Bandtlow et al, 1990;Fawcett et al, 1989;Moorman and Gould 1997). In vivo experiments demonstrated that elongation of axons over long distances could be observed in myelin-free spinal cord or optic nerve, which has been produced by killing the dividing oligodendrocyte precursors by repeated X-irradiation of newborn rats (Savio and Schwab 1990;Weibel et al, 1994) or by immunocytolysis in chicken (Hasan et al, 1993;Keirstead et al, 1992).…”
Section: Cns Myelin a Nonconducive Environment For Extending Neuritesmentioning
confidence: 99%